ARTEFATOS MESOPOTÂMICOS COMO POSSIBILIDADES DIDÁTICAS PARA O ENSINO DE MATEMÁTICA - TRINDADE, Thereza Cristinna Vieira (2024)
It is true that the discussion about the History of Mathematics in Mathematics teaching has been growing because it is seen as a strategic form of teaching with the power to awaken students' interest and curiosity to understand mathematics as a human construction that was developed over time by the needs of civilizations, until reaching the format it has today. By focusing on the Mesopotamian civilization, this research aims to investigate Mesopotamian mathematical artifacts and didactic possibilities for their use in teaching Mathematics in Basic Education. Using as a research methodology the delimitation of the research, selection of databases, development of search strategies and the selection and systematization of what was found. The choice of tablets is related to the fact that we found potential for them to be used in the classroom. We conducted qualitative, bibliographical and descriptive research on artifacts for teaching Mathematics, and thus found out what types of discussions were in existing works and which Mesopotamian artifacts were discussed and how many authors attributed their research relating artifacts to Mathematics teaching. We searched for national and international works to find out if new approaches or new artifacts had been translated, and the quantity of four works was analyzed and is part of our results. We attributed as a result the possible contents to be used and the teaching potential as a way to facilitate the use of the history of Mathematics through Mesopotamian artifacts.